Using Deep Learning Neural Networks to Solve Optimization Problems in Economy - Anh, Vu Tuan; Thuy Gang, Le Thi; Loan, Do Thi; Khanh, Pham Van (VNU Journal of Science: Mathematics - Physics; Vol 40 No 4, 2024)
Abstract: In this work, we have used multilayer neural networks to solve high-dimensional dynamic programming problems. We propose a deep learning algorithm to efficiently compute the overall solution for this class of problems. Importantly, our method does not rely on integral approximation but instead on derivative approximation. We evaluate the effectiveness of the proposed method through the standard neoclassical growth model. Optimization, HJB equation, machine learning, neural network.